Pengaruh Kredibilitas Endoser dan Kredibilitas Perusahaan Terhadap Niat Pembelian Dengan Pendekatan Dual Credibility Model (Riset Manajemen & Akuntansi, 2010)
This study is implemented in Surakarta. Respondent under this study are of 200 respondents taken by purposive sampling. Data collection tool used is questionnaire by which had been tested on the validity and reliability. Data analysis method is Structural Equation Modeling (SEM). Result of this study show that (1) Advertisement model credibility (Endorser Credibility) has a positive and significant influence on advertisement-related attitude with line coefficient 0f 0.543 (p = 0.000), (2) Cooperate credibility is positive and significant on advertisement-relative attitude with line coefficient of 0.264 (p = 0.000), (3) corporate credibility has a positive and significant on product-related attitude with the line coefficient of 0.277 (p = 0.000), (4) corporate credibility has positive and significant influence on purchase intention with the line coefficient of 0.458 (p = 0.000), (5) Advertisement-related attitude has positive and significant influence on product-related attitude with line coefficient of 0.598 (p = 0.000), (6) Product-related attitude has positive and significant influence on purchase intention with the line coefficient of 0.609 (p = 0.000), and (7) Advertisement-related attitude has no influence on purchase intention with the line coefficient of 0.050 (p = 0.613).